Developmental changes in pharyngeal swallowing acoustics: a comparison of adults and children - Hennessey, Neville; Fisher, G.; Ciccone, Natalie (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. This study examined developmental differences in the acoustics of pharyngeal swallowing. Thirty-one young children (M = 4.5 years) and 29 adults (M = 22.5 years) were recorded swallowing thin liquid and puree boluses. In comparison with adults, children showed longer total swallow sound duration and duration to peak intensity, as well as greater variability in the duration to peak intensity and mean of the averaged spectrum in Hz. Thin and puree boluses differed in measures of duration, intensity and frequency of the averaged sound spectrum, although these effects did not interact with age. The increased variability in swallowing observed in children paralleled that found in acoustic measures of vowel formants, although speech and swallowing acoustic measures were uncorrelated. Using Formant 2 frequency as a proxy measure of vocal tract length, the age differences in swallowing acoustics appear to be independent of physical size, although associations between duration to peak intensity and pharyngeal size warrant further investigation. These findings suggest acoustic measures of swallowing are sensitive to developmental status, possibly reflecting ongoing refinement of the pharyngeal swallow across childhood, and support continued research into the use of digital cervical auscultation as a tool to assess the efficiency and stability of the swallowing neuromuscular control system in children and adults.